E-SERVICE QUALITY, CUSTOMER SATISFACTION, AND REPURCHASE INTENTION: ANALYZING THE IMPACT ON E-COMMERCE PLATFORM - Putri, Putu Puspita Sari Sastradi; Setiawati, Cut Irna (Jurnal Aplikasi Manajemen, 2021)
This research measured the effect of e-service quality on e-consumer satisfaction which has an impact on repurchase intention. This research aims to describe how the e-service quality conducted by e-commerce, named Bukalapak, affected e-consumer satisfaction, which will impact Bukalapak repurchase intention. This research uses quantitative methods with descriptive analysis. This research sampling technique was non-probability sampling and invited 150 respondents purchased on Bukalapak more than once as experience. Regarding data analysis techniques, this research used descriptive analysis and PLS-SEM analysis through SmartPLS 3.0 software. Based on description analysis, the e-service quality impacts e-consumer satisfaction since e-commerce provider has been provided programs such as the clear direction of giving comments and purchase feedback through online and application. Unfortunately, the repurchase intention on the e-commerce platform is below expectation (under sales). SEM-PLS results showed that e-service quality has a significant impact on e-consumer satisfaction in using e-commerce platforms. E-service quality has a significant impact on repurchase and e-consumer satisfaction has an impact on repurchase intention in using Bukalapak. Based on the results, e-service quality impacts repurchase intention through e-consumer satisfaction as a mediating variable in e-commerce platforms.